An empirical study of politico-economic interaction in the US - Bruno S. Frey; Friedrich Schneider (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 1976)
Popularity and reaction functions as the main relationships between the economic and political sectors are theoretically derived and empirically estimated with quarterly data for the U.S. One of the purposes is to endogenize government behavior in macro-econometric models. Unemploymentj inflation (negatively) and the growth of consumption (positively) influence presidential popularity. The presidents who fear not to be reelected use in turn their policy instruments (public expenditures and jobs) to increase their popularity. There is also some indication that the presidents pursue ideological goals when they are confident to win the upcoming election.
Keywords: 330